AHP – SINGLE EXPONENTIAL SMOOTHING: PEMILIHAN DISTRIBUTOR TERHADAP DAMPAK PERMINTAAN PRODUK KOPI - Johan Alfian Pradana; Rizki Puspita Dewanti; Mohamad Fauzin Abdulloh; Andrean Pradana Hidayat (Universitas Airlangga, 2022)
The purpose of this study is to assess the performance of suppliers based on the AHP method at the highest weight level, the consistency level of supplier performance based on the smallest consistency value and predict demand with the selected value in the conversion in the kilogram model. The research methodology is quantitative integration of AHP- Single Exponential Smoothing. The data of this study is primary data covering the AHP of the questionnaire, secondary data covering the data of actual requests. This study states that the performance of suppliers includes Quality, Cost and Delivery with consistency with the smallest criteria, namely Delivery, Quality and Flexybility. Meanwhile, the demand prediction with a capacity of 1336 cups of arabica coffee was converted to a capacity of arabica coffee beans of 27 kg in April 2022. The implications of this study are expected to be carried out in determining the dumping factor is experiment with a dumping factor decision-making model that is adjusted to the needs of the TKP Coffee Shop. The suggestion of this study for researchers can then determine the estimated capacity of safety supplies and an economical ordering model.